Tecendo leituras no ensino médio: olhares docentes sobre concepções, práticas e formação de leitores - Pimentel, Líliam Maria Sampaio Santana (2023)
The research entitled "Weaving Readings in High School: Teachers' Views on Conceptions, Practices and Readers' Training" investigates how the teachers of Portuguese Language, working at Modelo Luís Eduardo Magalhães High School, in Feira de Santana, accept and comprehend the training of reading outside the school environment. And how this practice in classrooms allows the insertion of everyday reading perspectives, in a way that it does not interfere with the schedule previously established for the school year curriculum. The coexistence with the intergeneration enables dialogues that emphasize differences between habits, languages and choices, which may constitute conflicts, thus this research aims to analyze the way and intensity that the Portuguese Language teacher in High School commits, welcoming and consenting, the consolidated reading that this student already brings. Part of the objectives of this study is to identify the conceptions of reading and reader from the narrative experiences with the collaborators; discuss the reading practices and the possible reading motivators of the students; problematize the challenges and the possibilities of the pedagogical actions regarding the formation process of the critical and autonomous reader in High School. This research, which has a qualitative approach has two methodological moments, the first is theoretical, of literature review, which is anchored in authors who critically analyze different meanings of reading: Cosson (2020), Maria (2013), Petit (2009, 2010), Freire (2011); the mediation of reading, with Petit (2009) and Cosson (2020); Reading from the Printed Word to the Digital Text , with Abreu (2001 and 2004) and Chartier (1999); and the meanings of literature, with Cândido (2004) and Todorov (2010). The second part has an investigative character, with the application of a questionnaire to outline the profile of the research collaborators, and the conducting of semi-structured interviews with teachers of the language area who work in the curricular component of Portuguese Language to collect data to be investigated. Considering the pandemic time, the process of dialogue with the research collaborators took place in virtual mode, from the applications present on Google Platform, which are the Google Form and Google Meet and have Modelo Luís Eduardo High School as field of investigation. This study aims that the school, represented by the figure of the teacher, awakens the acceptance of different readings and supports and that it can promote greater reach of reading among high school students, because it is necessary that there is a consistent reading awareness so that the practices throughout the life of these students are valued. The research reveals that the majority of teachers presented the movement of awareness and change, with regard to reading and classroom practice based on the use of canonical books. Although they still do not appreciate the students’ reading choices, bringing from outside the school, which makes it difficult not to recognize other possibilities of reading practice in this stage of Basic Education.